Time Travels are Already Possible Nowadays - Antonov, Alexander A (European Journal of Applied Sciences, 2025)
The theme of time travels has now been successfully mastered mainly by science fiction writers. The official position of science on this problem is as follows: although the possibility of time travels by the laws of physics is not excluded – teleportation in quantum mechanics, “twin paradox” in the special theory of relativity, “mole burrows” in the general theory of relativity, etc. – it will not be possible to create a time machine either now or in the distant future. However, this article provides descriptions of time travel realisations that are already physically feasible on Earth now.